2011
DOI: 10.2217/pgs.11.114
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Genomic Predictors of Anti-TNF Response

Abstract: The introduction of anti-TNF therapy has dramatically improved the outlook for patients suffering from a number of inflammatory conditions including rheumatoid arthritis and inflammatory bowel disease. Despite this, a substantial proportion of patients (approximately 30-40%) fail to respond to these potentially toxic and expensive therapies. Treatment response is likely to be multifactorial; however, variation in genes or their expression may identify those most likely to respond. By targeted testing of varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 86 publications
0
42
1
Order By: Relevance
“…Pharmacogenetics A substantial proportion of patients (approximately 30-40%) fail to respond to anti-TNF-α therapy for non-uveitis indications. 103 The largest studies in uveitis report a non-response rate of approximately 20%. 76,131 Treatment response is likely dependent on many factors, including age, location and severity of uveitis, and type of TNF-α blocker employed.…”
Section: Use Of Concomitant Immunomodulatory Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacogenetics A substantial proportion of patients (approximately 30-40%) fail to respond to anti-TNF-α therapy for non-uveitis indications. 103 The largest studies in uveitis report a non-response rate of approximately 20%. 76,131 Treatment response is likely dependent on many factors, including age, location and severity of uveitis, and type of TNF-α blocker employed.…”
Section: Use Of Concomitant Immunomodulatory Agentsmentioning
confidence: 99%
“…Emerging genome-wide association studies suggest that there may be a number of genes with modest effects on treatment response rather than a few genes of large effect; 103 Infliximab is currently the anti-TNF-α agent used more often for the treatment of immunemediated uveitis. 80 The number of studies is particularly large for uveitis associated with two underlying conditions: Behçet disease and JIA.…”
Section: Use Of Concomitant Immunomodulatory Agentsmentioning
confidence: 99%
“…1). After the full-text review, 10 of these 18 articles were excluded because 2 of them were review articles [16,24], 3 articles had no exact statistics about polymorphisms [25][26][27], 1 reported duplicate data [28], 1 was irrelevant to biological agent [29], 3 were not related to TNFRSF polymorphisms [2,30,31]. Finally, in the current study, 8 eligible studies [32][33][34][35][36][37][38][39] that meet the inclusion criteria were included in our biologic-specific meta-analysis.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…This issue could be addressed by pharmacogenetic studies which are analysis of genetic variations and may be used to predict how a patient may react to a drug, from both a safety and an efficacy points of view. Large-scale genetic analysis is revealing key gene associations with responsiveness and side effects to TNF inhibitors [16]. For example, Lee et al showed that individuals carrying the IL-6-174 C allele show a poorer response to anti-TNF therapy for RA [17].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of anti-TNF-a drugs is through interruption of the interaction between TNF-a and its receptors, with subsequent interference with downstream signaling; thus, the investigation of several potential pharmacogenomic targets reviewed extensively by Prajapati et al includes the candidate gene encoding TNF-a, genes in the TNF-a signaling pathway, susceptibility genes associated with disease development and Genome Wide Association Studies (GWAS) [49].…”
Section: Biologicsmentioning
confidence: 99%